128k views
1 vote
​​​Shown below are the steps used to solve an equation.

5 - 3 (x - 1) = 4 - 7x
5 - 3x + 3 = 4 - 7x
8 - 3x = 4 - 7x
8 = 4 - 4x
x= -1
​Explain what is happening to the equation during each step in the solution.

User Rhino
by
5.0k points

1 Answer

2 votes

5 - 3 (x - 1) = 4 - 7x, initial equation

5 - 3x + 3 = 4 - 7x, distributing 3 (x - 1) to get 3x + 3

8 - 3x = 4 - 7x, adding 3 to 5 to get 8

8 = 4 - 4x, subtracting 3x from both sides of the equation

x= -1, substituting x for the only possible value to make the equation true.

User Sevas
by
5.4k points